2021
DOI: 10.1002/hup.2817
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome among patients receiving antipsychotic and antidepressant drugs

Abstract: Background: Patients with Restless Legs Syndrome (RLS) experience psychological distress and diminished quality of life. Antipsychotics and antidepressants are known to be linked to RLS. Aims:This study aims to investigate the presence of RLS in psychiatric patients who receive antipsychotic and antidepressant drugs and to determine potential risk factors for its occurrence.Methods: Two hundred patients who received antipsychotic and antidepressant drugs for more than 1 month were recruited from two tertiary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In this observational, cross-sectional study, we found RLS frequency in 25% of outpatients who received SSRI/SNRIs for 4–8 weeks which is higher than the RLS prevalence both in the general population (5.5%) (Ohayon and Roth, 2002) and also psychiatric inpatients reported between 16.4 and 19.7% (Hohl-Radke and Staedt, 2009; Weber et al , 2022). There is a wide variation in the RLS frequency between the studies, which could be attributable to differences in risk factors of study populations and the determination of RLS with different assessment tools (Nichols et al ., 2003; Innes et al ., 2011; Patatanian and Claborn, 2018; Elrassas et al ., 2022). Thus, the frequency of RLS in the current study could be affected by various factors, such as ethnicity, genetic factors, and socioeconomic status, in addition to SSRI/SNRI treatment (Innes et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this observational, cross-sectional study, we found RLS frequency in 25% of outpatients who received SSRI/SNRIs for 4–8 weeks which is higher than the RLS prevalence both in the general population (5.5%) (Ohayon and Roth, 2002) and also psychiatric inpatients reported between 16.4 and 19.7% (Hohl-Radke and Staedt, 2009; Weber et al , 2022). There is a wide variation in the RLS frequency between the studies, which could be attributable to differences in risk factors of study populations and the determination of RLS with different assessment tools (Nichols et al ., 2003; Innes et al ., 2011; Patatanian and Claborn, 2018; Elrassas et al ., 2022). Thus, the frequency of RLS in the current study could be affected by various factors, such as ethnicity, genetic factors, and socioeconomic status, in addition to SSRI/SNRI treatment (Innes et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The major therapeutic drugs for RLS are dopaminergic drugs, α 2 δ channel ligands, and opioid preparations [ 4 ]. Besides, iron and antidepressant drugs have an impact on the symptoms of RLS [ 14 , 15 ], and sedative and hypnotic drugs can affect the sleep score of patients, so the use of these drugs also needs to be registered.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic persistent RLS is defined as frequent and burdensome RLS symptoms occurring at least twice weekly. The management of chronic persistent RLS is focused on symptom alleviation and improving quality of life through addressing secondary causes of RLS, lifestyle modifications, non-pharmacological interventions, and pharmacotherapy (Garcia-Borreguero et al, 2016;Kolla et al, 2018;Elrassas et al, 2021). In patients with evidence of iron deficiency and serum ferritin <75 µ/L, supplementation with ferrous sulfate 325 mg with vitamin C 100 mg once or twice daily may improve RLS symptoms (Garcia-Borreguero et al, 2016;Allen et al, 2018;Silber et al, 2021).…”
Section: Restless Leg Syndromementioning
confidence: 99%
“…As RLS is common in the geriatric population, special attention to the implications or issues associated with RLS in this population is necessary (Table 1). For example, as older patients may have more medical co-morbidities or polypharmacy, it is critical to consider potential secondary causes of RLS by assessing for iron deficiency, renal disease and reviewing their medications (Kolla et al, 2018;Earley et al, 2021;Elrassas et al, 2021). The increased risk of nighttime falls due to nighttime ambulatory episodes is another important consideration (Kuzniar and Silber, 2007;Richards et al, 2021).…”
Section: Recent Updates In Managing Older Adults With Rlsmentioning
confidence: 99%